Kesadaran demokrasi - Afifah, Zahrotul (Maliki Interdisciplinary Journal, 2025)
This journal examines Democratic awareness which includes understanding and experiencing democratic values. It involves the awareness of individuals and society about their rights and obligations in a democratic system. Democratic awareness includes understanding of values ​​such as participation, freedom, and justice. In a democratic society, democratic awareness is very important to build a harmonious relationship between individuals, society, and the state. This awareness allows individuals to understand their rights and obligations, and to actively participate in the political process. Democratic awareness also involves experiencing the importance of freedom and justice. This means that individuals and society must understand that freedom and justice are rights that must be protected and fulfilled by the state. Thus, democratic awareness is an important concept in building a democratic and just society. This awareness allows individuals and society to understand their rights and obligations, and to actively participate in the political process to build a better society. This journal also emphasizes the importance of democratic awareness in order to build a harmonious relationship between individuals and the state.